An Empirical Study on Awareness and Factors Influencing Consumer Purchase Behaviour Towards Non- Prescription Drugs with Reference to Visakhapatnam District, Andhra Pradesh State, India - Sai Kishore BHANDEVUPURAPU; Suneetha RAPAKA (Communications of International Proceedings, 2022)
You are your own doctor “is the central theme of non-prescription drugs. As the pandemic broke down havoc all over the world, people started taking care of themselves with health and medication becoming the topmost priority for the world. Taking non-prescription drugs over a long period of time can lead to any number of dangerous effects like seizures, heart rhythm abnormalities and other complications. There are very few studies on the topic – Consumer behaviour towards non- prescription drugs and so the researchers have studied about this topic. The researchers have sampled this in the Visakhapatnam City of the Andhra Pradesh State in India. The population of Visakhapatnam is 2,278,000. At 90% Confidence Level, 5% Margin of Error, the sample to be considered is 269. Sample size used was 234. The findings are that there is no significant relationship between the awareness of the safety profile of the non-prescription drugs and its purchase. So, people should be made aware of the safety profile of the non-prescription drugs as if this is not taken care of will lead to disastrous consequences on the health of the people. Also in this research it was found that in most of the rural areas, people use non-prescription drugs and the people in the rural areas should be educated on the proper usage of these drugs. At the end of the day, it is health and happiness that matter and the researchers are      perusing this research to try for contributing towards a better world
Keywords: Non- Prescription Drugs; OTC drugs; Consumer awareness; drug safety